Big endothelin-1 as a clinical marker for ventricular tachyarrhythmias in patients with post-infarction left ventricular aneurysm - Xiaohui Ning; Zihe Yang; Xuerui Ye; Yanhua Si; Fang Wang; Xiaoli Zhang; Shu Zhang (Anatolian Journal of Cardiology, 2019)
Objective: Ventricular tachyarrhythmia is the leading cause of death in post-infarction patients. Big endothelin-1 (ET-1) is a potent vasoconstrictor peptide and plays a role in ventricular tachyarrhythmia development. The aim of this study was to investigate the association between the serum concentration of big ET-1 and ventricular tachyarrhythmia in post-infarction left ventricular aneurysm (PI-LVA) patients. Methods: A total of 222 consecutive PI-LVA patients who had received medical therapy were enrolled in the study. There were 43 (19%) patients who had ventricular tachycardia/ventricular fibrillation (VT/VF) at the time of admission. The clinical characteristics were observed and the plasma big ET-1 level was measured. Associations between big ET-1 and the presence of VT/VF were assessed. Patients were followed up to check for outcomes related to cardiovascular mortality, VT/VF attack, and all-cause mortality. Results: The median concentration of big ET-1 was 0.635 pg/mL. Patients with big ET-1 concentrations above the median were more likely to have higher risk clinical features. There was a positive correlation between the level of big ET-1 with VT/VF attack (r=0.354, p<0.001). In the multiple logistic regression analysis, big ET-1 (OR=4.06, 95% CI: 1.77-9.28, p<0.001) appeared as an independent predictive factor for the presence of VT/VF. Multiple Cox regression analysis suggested that big ET-1 concentration was independently predictive of VT/VF attack (OR=2.5, 95% CI 1.4–4.5, p<0.001). NT-proBNP and left ventricular ejection fraction of ≤35% were demonstrated to be independently predictive of cardiovascular mortality and all-cause mortality. Conclusion: Increased big ET-1 concentration in PI-LVA patients is a valuable independent predictor for the prevalence of ventricular tachyarrhythmias and VT/VF attacks during follow-up after PI-LVA treatment.